Information Systems Implementation, Stakeholder Perceptions and Organisational Change - Schoeman, Mark (My University, 2011)
This research report chronicles an expert system (ES) implementation at a large financial services firm in order to examine how individual stakeholders, party to an information systems (IS) implementation, perceive and experience change. A social constructivist orientation is used in conjunction with an adapted form of Leavitt’s (1965) organisational change model in order to deconstruct individual stakeholder perceptions and experiences. The research reveals that stakeholders perceived and experienced the implementation differently - based on their construction of individual and organisational reality. The research suggests that the success of an IS implementation may be enhanced if IS practitioners recognise the significant influence of constructed individual and organisational reality on the progression of an IS implementation, and the consequent impact on organisational performance
MBA - WBS
Keywords: Change management; Information systems implementation